2013
DOI: 10.13064/ksss.2013.5.4.081
|View full text |Cite
|
Sign up to set email alerts
|

L2 Proficiency Effect on the Acoustic Cue-Weighting Pattern by Korean L2 Learners of English: Production and Perception of English Stops

Abstract: This study explored how Korean L2 learners of English utilize multiple acoustic cues (VOT and F0) in perceiving and producing the English alveolar stop with a voicing contrast. Thirty-four 18-year-old high-school students participated in the study. Their English proficiency level was classified as either 'high' (HEP) or 'low' (LEP) according to high-school English level standardization. Thirty different synthesized syllables were presented in audio stimuli by combining a 6-step VOTs and a 5-step F0s. The liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Along these lines, Kang and Guion (2006) showed that native Korean speakers who had learned English later in life appeared to have merged the English voiceless and Korean aspirated categories in production; English voiced stops, on the other hand, appeared to be a distinct category from either Korean fortis or lenis stops (similar to fortis stops in terms of VOT, but similar to lenis stops in terms of f0). Similarly, Kong and Yoon (2013) showed that native Korean speakers with higher English proficiency made more effective use of VOT in distinguishing the English stop contrast, and that the high-proficiency group showed more native-English-like performance in perception as well. Further perceptual findings come from Schmidt (1996) and Park and de Jong (2008), who asked native Korean listeners to listen to English syllables and indicate the Korean consonant that best represented the syllable-initial sound.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Along these lines, Kang and Guion (2006) showed that native Korean speakers who had learned English later in life appeared to have merged the English voiceless and Korean aspirated categories in production; English voiced stops, on the other hand, appeared to be a distinct category from either Korean fortis or lenis stops (similar to fortis stops in terms of VOT, but similar to lenis stops in terms of f0). Similarly, Kong and Yoon (2013) showed that native Korean speakers with higher English proficiency made more effective use of VOT in distinguishing the English stop contrast, and that the high-proficiency group showed more native-English-like performance in perception as well. Further perceptual findings come from Schmidt (1996) and Park and de Jong (2008), who asked native Korean listeners to listen to English syllables and indicate the Korean consonant that best represented the syllable-initial sound.…”
Section: Introductionmentioning
confidence: 85%
“…Previous work has shown greater-than-native-like use of f0 (e.g. Kim 1994; Kang and Guion 2006; Kong and Yoon 2013); at the same time, work showing differences in L2-L1 mapping of the English to Korean contrast (e.g. Schmidt 1996; Park and de Jong 2008) suggests that there may be considerable variability in perceptual patterns.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, Korean speakers vary both VOT and f0 to an equal extent when distinguishing their L2 English stop contrast in production (Schertz et al, 2015), but this cue use is not necessarily reflected in their perception . The factors underlying these differences in phonetic structure are not yet known; however, recent work by Kong and Yoon (2013) suggests that listeners’ level of English proficiency plays a role, with higher-proficiency speakers using f0 less (i.e. in a more native-like way) than lower-proficiency speakers.…”
mentioning
confidence: 99%